Utilization of grinding dross remained from production process in order to minimize waste and save costs - Gulyás, Emese; Boros, Norbert (International Journal of Engineering and Management Sciences, 2016)
It is i mportant to reuse wastes from production process particulary. In the course of metal roughing grinding dross comes off. Its oil content is high enough to treat i t wi th piston briquette machinery and by this methode  part of this oil can be retrievable and returned to production. By means of making a ma terial balance I determined how much effective the machinery has to be to work the dross and its payback was also calculated.